THE EFFECT OF HUMAN RESOURCES COMPETENCY AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE THROUGH COMPENSATION AT PT. CONSERVATION TOURISM INDONESIA - Qowi Hibatullah; Yeni Absah; Abdul Rahim Matondang (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Economic development can sometimes be quite rapid in the current era of globalization, as seen from the increasing demand of society every year. People have to work hard to meet their needs, as seen from the tight competition both in industry and in the workplace. Population growth, decreasing job opportunities, and increasing poverty rates are the main causes of increasing economic demand in developing countries such as Indonesia. Therefore, society or human resources must have superior competence and quality in order to compete and survive in this highly competitive market.